2017
DOI: 10.1073/pnas.1701952114
|View full text |Cite
|
Sign up to set email alerts
|

Malate-dependent Fe accumulation is a critical checkpoint in the root developmental response to low phosphate

Abstract: Low phosphate (Pi) availability constrains plant development and seed production in both natural and agricultural ecosystems. When Pi is scarce, modifications of root system architecture (RSA) enhance the soil exploration ability of the plant and lead to an increase in Pi uptake. In Arabidopsis, an iron-dependent mechanism reprograms primary root growth in response to low Pi availability. This program is activated upon contact of the root tip with low-Pi media and induces premature cell differentiation and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(168 citation statements)
references
References 51 publications
10
153
0
Order By: Relevance
“…To estimate the effect of root illumination in this molecular response, we compared our data with those reported by Mora‐Macias et al . (), in which roots were grown in the presence of light. We found that only 29% of the upregulated transcripts and 22% of the downregulated transcripts were common between both datasets (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the effect of root illumination in this molecular response, we compared our data with those reported by Mora‐Macias et al . (), in which roots were grown in the presence of light. We found that only 29% of the upregulated transcripts and 22% of the downregulated transcripts were common between both datasets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphate starvation has a significant impact on global gene expression (Misson et al ., ; Bustos et al ., ; Woo et al ., ; Secco & Whelan, ; Mora‐Macias et al ., ). These analyses, together with genetic studies (Rubio et al ., ; Catarecha et al ., ; Ticconi et al ., ; Nussaume et al ., ; Gamuyao et al ., ; Wang et al ., ; Ruan et al ., ), have shed light on the molecular mechanisms that regulate the PSR.…”
Section: Discussionmentioning
confidence: 97%
“…Upon nitrogen depletion, roots secrete small C‐terminally Encoded Peptides (CEPs) which are translocated to the shoot and are perceived by leucine‐rich repeat receptor kinases (LRR‐RKs) to activate nitrate transporters such as NRT1.1 (Sun et al ., for a review; Tabata et al ., ). Recent additions to the list of foraging regulators include STOP1 and ALMT1 that mediate phosphate‐induced root remodeling through malate exudation (Balzergue et al ., ; Mora‐Macias et al ., ). Depending on the source of phosphate available in the soil, the grass Deschampsia cespitosa produces more biomass when grown with a different grass species than with conspecifics, suggesting that nutrient availability regulates plant competition (Ahmad‐Ramli et al ., ).…”
Section: Neighbour Detection and Response Strategiesmentioning
confidence: 97%
“…PDR2 encodes a P5-type ATPase, whereas LPR1/2 is a ferroxidase, which enables ROS generation and callose deposition in both the apoplast surrounding the stem cell niche (SCN) of the root apical meristem (RAM) and the root transition zone. Recently, it was also reported that mutants of other Al tolerance genes, stop1 and almt1, are both insensitive to Pi deficiency in terms of primary root growth inhibition (Balzergue et al, 2017;Mora-Mac ıas et al, 2017). The hsp10 allele is a loss-of-function allele of ALUMINUM SENSITIVE3 (ALS3), which encodes a half-size ABC transporter involved in Al resistance (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%